Ingatan Sosial, Trauma, dan “Maaf”: Sebuah Refleksi untuk Indonesia - Reza A.A Wattimena (Respons: Jurnal Etika Sosial, 2008)
The paper exposes the concept of social memory through three perspectives, namely philosophy, history, and social psychology. Social memory is the accumulation of individual memory, and beyond. It means that, social memory has its ontological status which is different to individual memory. Social memory contains both kind of memories of positive events in the past, and the memories of traumatic negative events. In Indonesia, the memory of traumatic events buried deeply. This act will change the social memory concerning traumatic events to social trauma. This kind of trauma will create further crises in Indonesia, e.g. the crises of identity.